Needleless Electrospinning Technology - An Entrepreneurial Perspective - Ramakrishnan, Ramprasath; Jolius, Gimbun; Fahmi, Samsuri; Vigneswaran, Narayanamurthy; Gajendran, Natarajan; Lakshmi, Yamini Sudha; Stranska, Denisa; Ranganathan, Balu (Informatics Publishing Limited, 2016)
Background/Objectives: Needleless electrospinning technology surmounts the shortcomings and bottlenecks of the conventional needle based electrospinning systems. Spinneret clogging and lower throughput in terms of productivity has been the setbacks of the conventional technology leading to fewer nanofibers based commercial products. Nanofiber based products finds a market in healthcare, energy and defence. Proof of concept leading to lab level prototype scaling up into industrial level of nanofiber production units is the focus of this paper. Methodology/Analysis: A simple search in the scopus web portal with a keyword 'electrospinning' resulted in 16,272 publications as of date. Same search for patent in US patent office portal resulted in 1939 granted patent documents. A comparison of years of technology time cycle (110 years), publications (16,272) and granted patents (1939) with the companies (31) working on electrospun products was made. Findings: Bubble, hollow tube, roller, wire based and slit-surface needleless electrospinning units are discussed on the basis of entrepreneurial product cycle of prototype development translating into commercial units. Nanofiber production at a mean diameter of 140 nm at commercial level using Poly (ethylene) oxide for Nano Drug Delivery Systems (NDDS) by wire based free surface electrospinning has been analysed. Novelty/Improvements: The analysis proves an entrepreneurial approach in the area of electrospinning as evidenced by number of patents match ups or exceeds publications in some region and also depicts its futuristic demand in several areas including healthcare and energy sectors.